Coenzyme Q10 and Endocrine Disorders: An Overview - David Mantle; Iain Parry Hargreaves (MDPI AG, 2023)
Mitochondrial dysfunction and oxidative stress have been implicated in the pathogenesis of a number of endocrine disorders; this, in turn, suggests a potential role for the vitamin-like substance coenzyme Q10 (CoQ10) in the pathogenesis and treatment of these disorders, on the basis of its key roles in mitochondrial function, and as an antioxidant. In this article we have therefore reviewed the role of CoQ10 deficiency and supplementation in disorders of the thyroid, pancreas, gonads, pituitary and adrenals, with a particular focus on hyperthyroidism, type II diabetes, male infertility and polycystic ovary syndrome.